Making a Difference - Szutkowski, Kuba; Vriend, Reinier (Netherlands, 2015)
In this documentary, the directors will fight for transparency in the elusive world of international volunteering which has gotten industry proportions. Not everything that volunteers are asked to do in far away places is aimed at the help of others and the interests of involved companies are often dubious.
Keywords: Documentary films